Elaboration of SOR and ECM Model in A Cashless Society Environment - Reza Riandani; Wira Bharata (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
The phenomenon of rapidly developing technology triggers the emergence of a cashless society culture that prefers to make digital transactions rather than cash. This study aims to determine Continuance Intention on a technology by using Perceived Usefulness, Perceived Ease of Use, Trust, and Satisfaction and implementing the Stimulus-Organism-Response Model and Expectation-Confirmation Model. The research type of this study is quantitative, using a correlational method. Respondents in this study were visitors to Samarinda Central Plaza who had used QRIS. Data was collected using purposive sampling and Structural Equational Model (SEM) as a data analysis technique. The results prove that all hypotheses are accepted, and in the mediation test, only Trust cannot mediate Perceived Usefulness on Continuance Intention. Keywords: Stimulus-Organism, Response Model, Expectation-Confirmation Model, Perceived Usefulness, Perceived Ease of Use, Trust, Satisfaction, Continuance Intention.